Determinants of participation in rural off-farm activities and effects on food shortage, relative deprivation and diet diversity - Tigabu Getahun; Gebeyehu Fetene (University of Bonn, Center for Development Research (ZEF), 2022)
This study investigates the determinants of smallholders' participation in rural off-farm activities, which includes rural non-farm own business and wage employment, and its effect on food shortage, relative deprivation and dietary diversity. To address these objectives, we use a three-wave panel dataset of 7,110 smallholder farm households in Ethiopia. The estimation result suggests that the gender composition of households, age, education, natural shocks, participation in community meetings, exposure to media, access to credit, farmland, agricultural markets and rural infrastructure such as electricity are the key determinants of smallholders' participation in rural off-farm activities. The estimation results also suggest that smallholders' participation in rural wage employment aggravates relative deprivation, while participation in rural non-farm own business activities reduce relative deprivation and food shortage. On the other hand, our estimation results indicate that participation in both nonfarm own business activities and wage employment improve the dietary diversity of smallholder farmers. Hence, well-designed policy interventions aimed at enhancing smallholder farmers' rural wage employment and non-farm own business participation could help to enhance dietary diversity and reduce food shortages and relative deprivation.
Keywords: J00; J20; J43; 330; Rural off-farm income; wage employment; non-farm own business; farm income; food shortage; relative deprivation; diet diversity